Novel Liposomal Formulation with Azelaic Acid: Preparation, Characterization, and Evaluation of Biological Properties - Paula Melania Pasca; Florina Miere (Groza); Angela Antonescu; Luminita Fritea; Florin Banica; Simona Ioana Vicas; Vasile Laslo; Dana Carmen Zaha; Simona Cavalu (Applied Sciences, 2022)
Azelaic acid (AA), as a natural product, was proven to be effective in targeting multiple causes of acne and related dermatological conditions, as it is well tolerated using different classical formulations (gel, cream, etc.). However, its limited aqueous solubility and inadequate penetration across the stratum corneum might be related to different possible side effects such as itching and burning. The aim of our work was to elaborate a novel liposomal formulation based on azelaic acid, with enhanced biocompatibility, bio-availability, antimicrobial, antigenotoxic, and anti-inflammatory properties. The liposomal formulations were prepared by the lipid film hydration method with different concentrations of azelaic acid (15%, 20%, 25%) and characterized in terms of morphological features, physico-chemical properties, antimicrobial, cytotoxic, and in vitro wound healing effect. Successful encapsulation with 80.42% efficiency, with a size of up to 500 nm and good stability, was achieved, as demonstrated by FTIR spectroscopy (Fourier Transform Infrared Spectroscopy), DLS (dynamic light scattering), and zeta-potential measurements. In terms of antibacterial activity, all the liposomal formulations exhibited a better effect compared to free AA solution against Staphylococcus aureus and Enterococcus faecalis. Cytotoxicity assays and an in vitro “scratch” test performed with normal human dermal fibroblasts revealed an accelerating healing effect, while a comet assay evidenced the protective effect of AA liposomal formulations against hydrogen-peroxide-induced DNA damage in fibroblasts. The optimum formulation in terms of both the antimicrobial and wound healing effect was AALipo20% (liposomes with 20% azelaic acid included).